Catalytic Asymmetric Cycloaddition of In Situ-Generated ortho-Quinone Methides and Azlactones by a Triple Brønsted Acid Activation Strategy - Yu, Xiao-Ye; Chen, Jia-Rong; Wei, Qiang; Cheng, Hong-Gang; Liu, Zhi-Cheng; Xiao, Wen-Jing (Chemistry : a European journal, 2016)
A convergent and highly stereoselective [4+2] cycloaddition of in situ‐generated ortho‐Quinone methides (o‐QMs) and azlactone enols has been successfully developed through a triple Brønsted acid catalysis strategy. This protocol provides an efficient and mild access to various densely functionalized dihydrocoumarins bearing adjacent quaternary and tertiary stereogenic centers in high yields with excellent diastereo‐ and enantioselectivity. Triple activation! A convergent and highly stereoselective [4+2] cycloaddition of in situ generated ortho‐Quinone methides (o‐QMs) and azlactone enols has been successfully developed through a triple Brønsted acid catalysis strategy. This protocol provides an efficient and mild access to various densely functionalized dihydrocoumarins (see scheme).